Prof. Malik Hussain Mubbashar - Minhas, Fareed Aslam; Rana, Mowadat Hussain (Journal of Pakistan Psychiatric Society, 2020)
How does one pay homage to the person who made you who you are? How does one come to terms with the death of the mentor who is a permanent part of your own being? The eyes that showed you the world for what it is, the ears that attuned you to hear what is worth paying heed to, and the mind that forever changed the way you think; how does one bereave their departure? The two authors of this obituary of Prof Malik Hussain Mubbashar, Sitara e Imtiaz, Hilal e Imtiaz (Civil) are mere representatives of academic and spiritual progeny that runs in thousands. We have taken ourselves to record on their behalf the arduous task of encompassing his achievements, and giving a glimpse into a life well-led for our readers.